THE INFLUENCE OFINTELLECTUAL INTELLIGENCE AGAINST STUDENTS' ACHIEVEMENTINMATHEMATICS - Fitriyani Hali; Muh. Iqbal Heryanto (USN Kolaka, 2017)
This study aimed to determine: (1) the level of intellectual intelligence of students. (2) the level of student's mathematics learning achievement. (3) the presence or absence of significant influence of intellectual intelligence on student's mathematics learningachievement. This research was conducted on 12 April until 29 April 2013 which is located at SMP Negeri 2 Wundulako. The population in this study were all students of class VIII SMP Negeri 2 Wundulako Lesson Year 2012/2013 which amounted to 110people, where the samples used by researchers as much as 25% that is 28 people by using random sampling method. Data collection techniques for intellectual intelligence variables using intelligence test results, while for learning achievement variable using the value of report cards. Data analysis techniques used were statistical analysis and inferential statistical analysis. From the results of the study indicated that: (1) No students (0%) had intelligence on intelligent and very intelligent category, 1 student(3.75%) had intelligent intellectual intelligence, 5 students (17,86 %) had intelligent intellectual intelligence, 19 students (67.86%) had moderate intellectual intelligence, 1 student (3.57%) had average intellectual intelligence, 2 students (0% ) had less intellectual intelligence, and no students (0%) had very little intellectual intelligence; (2) The achievement of students' mathematics learning was in good category with the amount of 1 student (3,57%) had high learning achievement of math, 25 students (89,29%) got moderate learning achievement, 2 students 7.14%) got low mathematics learning achievement, and no students (0%) had very low mathematics learning achievement; (3). There was a significant influence between students' intellectual intelligence on mathematics learning achievement of students of grade VIII SMP Negeri 2 Wundulako.